PERSEPSI DAN SIKAP MASYARAKAT TERHADAP PENERAPAN PROGRAM PEMBERDAYAAN DI SEKITAR SUB DAERAH ALIRAN SUNGAI MIU (KASUS PROGRAM SCBFWM DI DESA SIMORO KECAMATAN GUMBASA KABUPATEN SIGI) - Satriani, Satriani; Golar, Golar; Ihsan, Moh. (Universitas Tadulako, 2013)
The purpose of this study was to determine the public perception and response on the Strengthening Community-based Forest and Watershed Management (SCBFWM) programs. The research was conducted in the Sub DAS Miu, village of Simoro, Gumbasa District, Sigi Regency, Central Sulawesi, from May through Juni 2013. Primary and secondary data were collected by using questionnaires and in-depth interviews on respondents. The total number of respondents were fourty. The main respondent was determined by using purposive sampling method, with the consideration that the respondent is stakeholder that directly involved in the SCBFWM programs. The results showed that communities had high understanding on SCBFWM programs. Further, the perception and response of communities were also categorized in high level. It is indicated that communities were favourable on that programs. Based on the Likert scale, the response of communities on the SCBFWM programs was also classified to strong and very good level. Keywords: Perception, Response, Respondent, SCBFWM, Sub DAS Miu